Tracking sedimentation process under progressive mangrove propagation in low-energy bays - Weiming Li; Zhijun Dai; Xuefei Mei; Jiejun Luo; Wenjun Zeng; Ping Zhang; Ran Chen; Jinping Cheng (Marine Geology, 2026)

Pretreatment-driven component-oriented conversion and microbial community assembly: Selective regulation of coupled methane and vivianite recovery in anaerobic digestion - Lulu Dai; Shaoyang Ma; Ping Zhang; Xianhong Wang; Bo Dong; Yixin Liu; Weihua Li (Journal of Environmental Chemical Engineering, 2026)

A mechanism-guided, low-input Lactiplantibacillus plantarum strategy for attenuating antibiotic resistomes under oxygen re-entry during anaerobic fermentation - Chaosheng Liao; Mingjie Zhang; Wenlong Dai; Xiaolong Tang; Pan Wang; Ning Mao; Ping Li (Chemical Engineering Journal, 2026)

Pesticide exposure in Eriocheir sinensis: Oxidative stress, endocrine disruption, gut–hepatopancreas axis impairment, and systems toxicology - Shi-Rong Li; Dan-Dan Bian; Xiang Lu; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Effects of dietary rosemary extract on meat quality, antioxidant capacity, fatty acid and amino acid compositions, and proteomic profile of duck breast muscle - Yang Liu; Xuan Huang; Chuang Li; Ping Deng; Xu Zhang; Yan Hu; Qiuzhong Dai (Food Chemistry, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Multi-phase fate and removal mechanism of acetamiprid in a planted coastal wetland mesocosm system: A ‘dual-engine’ perspective - Li Lu; Jing Zhao; Yufei Dai; Xin Luo; Zengyuan Niu; Ping Wang; Xiulin Wang; Keqiang Li (Journal of Hazardous Materials, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Next-generation chitosan biodegradable films reinforced with bioactive acid-DES: A sustainable solution for improved mechanical, antibacterial, and anti-browning properties - Dehong Lu; Huimin Yao; Nouman Ali Shah; Sajid Ali; Li-Yan Zeng; Ping Shi; Yuan-Sen Liu; Ziru Dai; Hafiz Umer Javed (Carbohydrate Polymers, 2026)

Comparative analysis of chemical composition in Zanthoxylum avicennae leaves and branches based on UPLC-Q-Orbitrap HRMS, and evaluation of their antioxidant activities - Liang-Qian Zhang; Yuan Tian; Li-Ping Dai; Xing-Er Ye; Yi-Qin Zheng; Nan-Chen Lai; Wei Dai; Qi Wang (Natural Product Research, 2026)

Insight into the thermodynamic response characteristics in a liquid helium-4 tank using a modified Lee model: A numerical study - Caigong Zhang; Shaomu Wen; Zhixiang Dai; Changjun Li; Ping Tang; Wenyan Zhang; Xue Zhong; Yang Peng (Process Safety and Environmental Protection, 2026)

In-situ tar reduction and catalytic reforming in sewage sludge gasification using steel slag oxygen carrier - Quxiu Dai; Qianrong Zhang; Nanqi Ren; Jiawei Li; Qihong Cen; Wang Du; Longgui Xie; Liping Ma; Ping Ning; Binbin He (Bioresource Technology, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

The degradation pathway and removal effectiveness of atrazine in a Photocatalysis–Microorganism combined system in coastal wetlands - Yufei Dai; Jing Zhao; Li Lu; Jingyu Zhang; Mengxue Xing; Haoyu Zhang; Xin Luo; Zengyuan Niu; Ping Wang; Keqiang Li (Journal of Environmental Management, 2026)

Analysis of Seasonal Propagation Dynamics and the Potential Driving Factors from Meteorological to Soil Moisture Drought - Meng Dai; Ping Feng; Jianzhu Li; Renjie Tao (Water Resources Management, 2026)

Metabolomic analysis of coloration mechanism of bamboo sheaths in different cultivars of Chimonobambusa utilis - Yan Lan; Xiao Zhu; Guang-Qian Gou; Ai-Juan Tan; Zhao-Xia Dai; Shi-Ping Huang; Gui-Li Yang (Physiology and Molecular Biology of Plants, 2026)

Anthropogenic disturbances drive stepwise geomorphic changes of shoal-channel systems in a tide-dominated estuary - Ping Zhang; Linxi Fu; Xiangyuan Li; Jianliang Lin; Huayang Cai; Zhijun Dai; Qingshu Yang (Marine Geology, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Breaking the Alzheimer’s Treatment Stalemate: Synergistic Application Strategies of Nanomaterials and Pharmaceutical Agents - Han Gao; Fangyuan Cheng; Zihan Zhang; Bo Yan; Pan Liao; Shishuang Zhang; Dai Li; Fanglian Chen; Ping Lei (Molecular Neurobiology, 2026)

Granulated Organic Amendment Enhances Soil Fertility, Alleviates Microbial Metabolic Limitation, and Increases Rice Yield in a Medium and Low-Yield Paddy Fields of Subtropical China - Yingnan Xian; Yan Li; Zhe Li; Mingxia Wang; Yuting Dai; Baozhen Li; Ping Zhou; Wei Gao; Xiaobin Guo; Jinshui Wu (Journal of Soil Science and Plant Nutrition, 2025)

Application of magnetic amplitude inversion in the identification of igneous rocks in superimposed basins: a case study in Qikou depression - Shu-ling Li; Jirigalatu; Xue-ping Dai (Applied Geophysics, 2025)

A new cage design to test pesticide impacts on honey bees via toxicant exposure through sucrose, pollen and beeswax simultaneously - Cameron J. Jack; Cody Prouty; Gerbson A. Mendonça; Ping Li Dai; Jeffrey R. Bloomquist; James D. Ellis (Environmental Research, 2025)

Efficient room-temperature hydrolytic cleavage of CS2 via Pd-anchored polynitrogen porous polymers - Kai-Wen Jiang; Xing-Yu Chen; Xiao-Li Jiang; Qing-Ya Sun; Yu-Peng Dai; Hui-Zhen He; Ying Zhou; Ping Shang; Xuan-Feng Jiang (Journal of Hazardous Materials, 2025)

Experimental and theoretical calculation study on phosphorus removal by nZVI-loaded biochar/active clay: Synergism of chemical bonding and coordination - Tong Hao; Chen Zhao; Mingyu Shan; Yubo Ding; Kongna Wu; Xing Dai; Juan Li; Ping Zeng (Journal of Environmental Chemical Engineering, 2025)

Enhanced aerobic granular sludge cultivation in continuous-flow membrane bioreactors: Evaluating a novel vertical circulation configuration and multi-mechanism approach - Tenglong Dai; Mengci Ni; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Journal of Environmental Chemical Engineering, 2025)

Comparison of surface energy balance and melt characteristics between debris-covered and debris-free zones on Qingbingtan Glacier No. 72, Mt. Tomor of Tien Shan - Jie He; Puyu Wang; Hongliang Li; Ping Zhou; Jianxin Mu; Fanglong Wang; Puchen Chen; Fengchen Yu; Yuping Dai (Climate Dynamics, 2025)

Osthole inhibits proliferation and induces autophagy-dependent ferroptosis of cervical cancer cells through induction of TFR1 - Linjun Li; Yue Zhao; Xiaojuan Li; Muzhao Tian; JiaoQing Wei; Wanyu Xie; Caishan Liu; Ping Dai; Juan Wang (Food and Chemical Toxicology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

Dose-dependent effects of MIL-88A(Fe) and MIL-101(Fe) on arsenic immobilization and phytoremediation using ramie (Boehmeria nivea L.) - Jian Ye; Xingyan Yin; Chunping Yang; Xiaofei Tan; Chuang Li; Gaobin Chen; Ping Chen; Qiang Chen; Mingyang Dai (Chemical Engineering Journal, 2025)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

Spatial distribution of soil organic carbon and its drivers in the Shandong section of the yellow river basin, China - Ping Dai; Liyuan Yang; Zenghui Wang; Jierui Dai; Jialiang Li (Journal of Soils and Sediments, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Transcriptome analysis reveals the mechanism of cortisol through GR regulating the expression of inflammatory cytokines in Siberian sturgeon (Acipenser baerii) after LPS treatment in vitro - Peng Tang; Yinqiu Chen; Defang Chen; Hao Zhu; Shaotong Dai; Jiawen Zhou; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Comparative analysis of volatile compounds of an oyster enzymatic hydrolysate adsorbed by V-type starches based on electronic nose, GC-IMS, and GC-MS - Peichao Chen; Yaolin Dai; Wuyin Weng; Zhongyang Ren; Ping Li; Linfan Shi (Food Research International, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Genomic selection of resistance to acute hepatopancreatic necrosis disease in Litopenaeus vannamei - Mianyu Liu; Xupeng Li; Jie Kong; Xianhong Meng; Kun Luo; Juan Sui; Ping Dai; Jian Tan; Jiawang Cao; Baolong Chen; Hongjie Wang; Sheng Luan (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Design and evaluation of C18 stationary phases with different polar-embedded groups for liquid chromatography - Xiao-Dong Cheng; Zheng Zhang; Yun-Ping Li; Xue-xin Dai (Analytica Chimica Acta, 2025)

Key process of ethanol hydrogen donor promoting the conversion of organic matter in sludge to bio-oil - Quxiu Dai; Linglong Zeng; Qihong Cen; Wang Du; Ping Ning; Kai Li; Zhiying Guo; Ran Ao; Longgui Xie; Nanqi Ren; Liping Ma; Jie Yang; et al. (Water Research, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

ent-Kaurane diterpenoids from Isodon henryi and their anti-inflammatory activities - Yi-xiao Li; Jun Chi; Ling-xia Zhang; Fang Wang; Wei-jin Zhang; Zhi-min Wang; Li-ping Dai (Phytochemistry, 2024)

Eco-friendly, stable, and high-performance biochar prepared by a twice-modification scheme: Saccharification of raw materials & thermal air oxidation of biochar - Yundong Liu; Bu Li; Wang Kai Tong; Han Tang; Zhaoli Ping; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2024)

Advances on a SPTC/JTC/ADR system for sub-Kelvin cooling - Zhichao Chen; Ping Liu; Yanan Li; Lei Ding; Zhenhua Jiang; Shaoshuai Liu; Yinong Wu; Wei Dai (International Journal of Refrigeration, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Vegetation restoration enhancing soil carbon sequestration in karst rocky desertification ecosystems: A meta-analysis - Wei Zheng; Xiaobin Guo; Ping Zhou; Li Tang; Jiaxin Lai; Yuting Dai; Wende Yan; Jinshui Wu (Journal of Environmental Management, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Study on regulation and effect mechanism of fish collagen peptide on retrogradation of corn starch gel - Yunfei Dai; Shuhan Zhang; Jinlei Li; Zhangzhang Li; Ninghua Deng; Yong Liu; Ping Wang; Dejian Huang; Yue Li (Food Bioscience, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Microbial metabolic capacity regulates the accrual of mineral-associated organic carbon in subtropical paddy soils - Zhe Li; Xun Duan; Xiaobin Guo; Wei Gao; Yan Li; Ping Zhou; Qihong Zhu; Anthony G. O'Donnell; Ke Dai; Jinshui Wu (Soil Biology and Biochemistry, 2024)

Experimental study on the synergistic strategy of liquid nitrogen and water mist for fire extinguishing and cooling of lithium-ion batteries - Ping Ping; Xinzeng Gao; Depeng Kong; Wei Gao; Zhenkai Feng; Can Yang; Chentong Li; Xinyi Dai (Process Safety and Environmental Protection, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Multiple stresses induced by chronic exposure to flupyradifurone affect honey bee physiological states - Jin Chen; Yong-Jun Liu; Qiang Wang; Li Zhang; Sa Yang; Wang-Jiang Feng; Min Shi; Jing Gao; Ping-Li Dai; Yan-Yan Wu (Science of The Total Environment, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Esterified wheat bran: Physicochemical properties, structure and quality improvement of Chinese steamed bread during refrigerated storage - Hua Li; Qingfeng Wu; Yanyan Guo; Ya Dai; Yali Ping; Zhenzhen Chen; Beibei Zhao (Food Chemistry, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

Multistage and diverse melt-mantle interaction in dunite-harzburgite channel systems beneath oceanic slow-ultraslow spreading centers: Evidence from the Xigaze ophiolite (Tibet) - Li Wang; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Lian-Rong Tian; Xiang Zhou (Lithos, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Formation and prolonged preservation of dense arc root cumulates: insights from retrograded eclogite xenoliths in the western Yangtze craton - Min Wang; Jian-Ping Zheng; Hong-Kun Dai; Qing Xiong; Yi-Xiong Li; Jin-Wei Guo (Contributions to Mineralogy and Petrology, 2024)

Selective adsorption of volatile compounds of oyster peptides by V-type starch for effective deodorization - Yaolin Dai; Zhongyang Ren; Ping Li; Yucang Zhang; Wuyin Weng; Linfan Shi (Food Hydrocolloids, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Prediction of meat yield in the Pacific whiteleg shrimp Penaeus vannamei - Ping Dai; Dongyan Li; Juan Sui; Jie Kong; Xianhong Meng; Sheng Luan (Aquaculture, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Acute and chronic effects of sublethal neonicotinoid thiacloprid to Asian honey bee (Apis cerana cerana) - Min Shi; Yi Guo; Yan-Yan Wu; Ping-Li Dai; Shao-Jun Dai; Qing-Yun Diao; Jing Gao (Pesticide Biochemistry and Physiology, 2023)

Evaluation on the rejuvenation and diffusion characteristics of waste cooking oil on aged SBS asphalt based on molecular dynamics method - Huanan Yu; Jinguo Ge; Guoping Qian; Chao Zhang; Wan Dai; Ping Li (Journal of Cleaner Production, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Identification and expression profiling of receptor‐interacting serine/threonine‐protein kinase 2 in Siberian sturgeon ( Acipenser baerii ) - Lu Lu; Shaotong Dai; Hao Zhu; Xin Zhang; Zhiqiong Li; Xiaoli Huang; Ping Ouyang; Yi Geng; Defang Chen (Journal of Fish Biology, 2023)
Receptor‐interacting serine/threonine‐protein kinase 2 (RIPK2) is an adaptor protein of the pattern recognition receptors NOD1 and NOD2 involved in regulating inflammatory response and resisting pathogenic microbial infection. In this study, Acipenser baerii RIPK2 ( AbRIPK2 ) was identified. The open reading frame of AbRIPK2 was 1815 bp encoding 604 amino acids. AbRIPK2 possessed the typical N‐terminal kinase domain (KD) and C‐terminal caspase recruitment domain (CARD). The phylogenetic tree analysis revealed that AbRIPK2 shared a relatively high identity with bony fish. Real‐time fluorescence quantitative PCR (qRT‐PCR) results indicated that AbRIPK2 was highly expressed in the gill, followed by muscle, liver and heart. AbRIPK2 was significantly induced in the spleen and valvular intestine after Streptococcus iniae and Aeromonas hydrophila infection. AbRIPK2 was significantly upregulated after peptidoglycan (PGN) treatment in the splenic leukocytes. This study indicated that AbRIPK2 played a potential role in resisting the pathogenic infection of Siberian sturgeon by responding to bacteria.

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Genetic Control of the Root System Traits in Oilseed Rape Under Contrasting Phosphate Supply Conditions by Genome-wide Association Study - Ping Xu; Xiaohua Wang; Hui Li; Shengjie Dai; Xue Cao; Zhenning Liu (Plant Molecular Biology Reporter, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

Synergistic inhibitory effect of berberine and icotinib on non-small cell lung cancer cells via inducing autophagic cell death and apoptosis - Ping Chen; Chun-Hua Dai; Zhi-Hao Shi; Yi Wang; Jian-Nong Wu; Kang Chen; Jin-Yu Su; Jian Li (Apoptosis, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Exploring soil erosion trajectories and their divergent responses to driving factors: a model-based contrasting study in highly eroded mountain areas - Chong Jiang; Zhiyuan Yang; Minting Li; Jialing Dai; Xinchi Wang; Haiyan Zhang; Long Yang; Lingling Zhao; Meili Wen; Ping Zhou (Environmental Science and Pollution Research, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

MdHAL3, a 4′-phosphopantothenoylcysteine decarboxylase, is involved in the salt tolerance of autotetraploid apple - Shuang Yang; Feng Zhang; Yangshu Wang; Hao Xue; Qiu Jiang; Jiajun Shi; Hongyan Dai; Zhihong Zhang; Linguang Li; Ping He; Yuanyuan Li; Yue Ma (Plant Cell Reports, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Comparing four methods of rearing Varroa destructor in vitro - Cameron J. Jack; Ping-Li Dai; Edzard van Santen; James D. Ellis (Experimental and Applied Acarology, 2020)

Predicting plant–soil N cycling and soil N2O emissions in a Chinese old-growth temperate forest under global changes: uncertainty and implications - Weiwei Dai; Edith Bai; Wei Li; Ping Jiang; Guanhua Dai; Xingbo Zheng (Soil Ecology Letters, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)

The Verticillium dahliae Sho1‐MAPK pathway regulates melanin biosynthesis and is required for cotton infection - Jun‐Jiao Li; Lei Zhou; Chun‐Mei Yin; Dan‐Dan Zhang; Steven J. Klosterman; Bao‐Li Wang; Jian Song; Dan Wang; Xiao‐Ping Hu; Krishna V. Subbarao; Jie‐Yin Chen; Xiao‐Feng Dai (Environmental Microbiology, 2019)
Summary Verticillium dahliae is a soil‐borne fungus that causes vascular wilt on numerous plants worldwide. The fungus survives in the soil for up to 14 years by producing melanized microsclerotia. The protective function of melanin in abiotic stresses is well documented. Here, we found that the V . dahliae tetraspan transmembrane protein VdSho1, a homolog of the Saccharomyces cerevisiae Sho1, acts as an osmosensor, and is required for plant penetration and melanin biosynthesis. The deletion mutant Δ Sho1 was incubated on a cellophane membrane substrate that mimics the plant epidermis, revealing that the penetration of Δ Sho1 strain was reduced compared to the wild‐type strain. Furthermore, VdSho1 regulates melanin biosynthesis by a signalling mechanism requiring a kinase‐kinase signalling module of Vst50‐Vst11‐Vst7. Strains, Δ Vst50 , Δ Vst7 and Δ Vst11 also displayed defective penetration and melanin production like the Δ Sho1 strain. Defects in penetration and melanin production in Δ Sho1 were restored by overexpression of Vst50 , suggesting that Vst50 lies downstream of VdSho1 in the regulatory pathway governing penetration and melanin biosynthesis. Data analyses revealed that the transmembrane portion of VdSho1 was essential for both membrane penetration and melanin production. This study demonstrates that Vst50‐Vst11‐Vst7 module regulates VdSho1‐mediated plant penetration and melanin production in V . dahliae , contributing to virulence.

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Coexpression of FOXK1 and vimentin promotes EMT, migration, and invasion in gastric cancer cells - Hui Zhang; Xiaosheng Wu; Yizhi Xiao; Liqing Wu; Ying Peng; Weimei Tang; Guangnan Liu; Yong Sun; Jing Wang; Huiqiong Zhu; Mengwei Liu; Wenjing Zhang; et al. (Journal of Molecular Medicine, 2019)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Antiplatelet Strategies and Outcomes in Patients with Noncardioembolic Ischemic Stroke from a Real-World Study with a Five-Year Follow-Up - Huimin Xu; Yanting Ping; Haoran Lin; Ping He; Wenlu Li; Haibin Dai (Translational Stroke Research, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

On the variability of near-bed floc size due to complex interactions between turbulence, SSC, settling velocity, effective density and the fractal dimension of flocs - Yang Yang; Ya Ping Wang; Chunyan Li; Shu Gao; Benwei Shi; Liang Zhou; Dandan Wang; Gaocong Li; Chen Dai (Geo-Marine Letters, 2016)

Sediment resuspension in tidally dominated coastal environments: new insights into the threshold for initial movement - Yang Yang; Ya Ping Wang; Shu Gao; Xiao Hua Wang; Ben Wei Shi; Liang Zhou; Dan Dan Wang; Chen Dai; Gao Cong Li (Ocean Dynamics, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Travel motivation of domestic tourists to the Changbai Mountain Biosphere Reserve in Northeastern China: A comparative study - Xiao-ping Gu; Bernard J. Lewis; Yan-quan Li; Da-pao Yu; Li Zhou; Wang-ming Zhou; Sheng-nan Wu; Li-min Dai (Journal of Mountain Science, 2015)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Deforestation and fragmentation of natural forests in the upper Changhua watershed, Hainan, China: implications for biodiversity conservation - De-Li Zhai; Charles H. Cannon; Zhi-Cong Dai; Cui-Ping Zhang; Jian-Chu Xu (Environmental Monitoring and Assessment, 2015)

Myocardial infarction worsens glomerular injury and microalbuminuria in rats with pre-existing renal impairment accompanied by the activation of ER stress and inflammation - Zhifeng Dong; Penglong Wu; Yongguang Li; Yuan shen; Ping Xin; Shuai Li; Zhihua Wang; Xiaoyan Dai; Wei Zhu; Meng Wei (Molecular Biology Reports, 2014)

Vertical distribution of bacterial communities in high arsenic sediments of Hetao Plain, Inner Mongolia - Yanhong Wang; Ping Li; Dawei Jiang; Bing Li; Xinyue Dai; Zhou Jiang; Yanxin Wang (Ecotoxicology, 2014)

Comparative survey of bacterial and archaeal communities in high arsenic shallow aquifers using 454 pyrosequencing and traditional methods - Ping Li; Dawei Jiang; Bing Li; Xinyue Dai; Yanhong Wang; Zhou Jiang; Yanxin Wang (Ecotoxicology, 2014)

Microbial transformation of the anti-diabetic agent corosolic acid - Xu Feng; Dai-Ping Li; Ze-Sheng Zhang; Zhi-Yong Chu; Jie Luan (Natural Product Research, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

Cycloartane-type triterpene glycosides from Beesia calthaefolia and their anticomplement activity - Li-Hua Mu; Hong-Jie Li; Dai-Hong Guo; Jin-Yuan Zhao; Ping Liu (Journal of Natural Medicines, 2014)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

New eudesmane-type sesquiterpenoid from Solanum lyratum with cytotoxic activity - Xiu-Ping Nie; Fang Yao; Xi-Dian Yue; Gui-Sheng Li; Sheng-Jun Dai (Natural Product Research, 2014)

Bacillus thuringiensis subsp. sichuansis strain MC28 produces a novel crystal protein with activity against Culex quinquefasciatus larvae - Peng Guan; Xiaojuan Dai; Jun Zhu; Qiao Li; Shuangcheng Li; Shiquan Wang; Ping Li; Aiping Zheng (World Journal of Microbiology and Biotechnology, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Early Carboniferous intra-oceanic arc and back-arc basin system in the West Junggar, NW China - Ping Shen; Hongdi Pan; Wenjiao Xiao; Xian-hua Li; Huawu Dai; Heping Zhu (International Geology Review, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Lowered Nudix type 5 (NUDT5) expression leads to cell cycle retardation in HeLa cells - Li-Qun Zhang; Da-Peng Dai; Wei Gan; Yasumitsu Takagi; Hiroshi Hayakawa; Mutsuo Sekiguchi; Jian-Ping Cai (Molecular and Cellular Biochemistry, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Characterization of the Hormone and Stress-Induced Expression of FaRE1 Retrotransposon Promoter in Strawberry - Ping He; Yue Ma; Hongyan Dai; Linguang Li; Yuexue Liu; He Li; Guiling Zhao; Zhihong Zhang (Journal of Plant Biology, 2012)

A New Genotyping Method for Detecting Low Abundance Single Nucleotide Mutations Based on Gap Ligase Chain Reaction and Quantitative PCR Assay - Ping Yi; Hongmei Jiang; Li Li; Faguo Dai; Yingru Zheng; Jian Han; Zhuqin Chen; Jianxin Guo (Cell Biochemistry and Biophysics, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Prevalence, intensity and associated factor analysis of Tropilaelaps mercedesae infesting Apis mellifera in China - Qi Hua Luo; Ting Zhou; Ping Li Dai; Huai Lei Song; Yan Yan Wu; Qiang Wang (Experimental and Applied Acarology, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Characterization of human embryonic stem cell-derived hematopoietic progenitor phenotype - Hai-Yang Zhou; Xiao-Yi Yang; Li-Jian Tao; Yue-Tian Chang; Ru-Ping Dai (In Vitro Cellular & Developmental Biology - Animal, 2010)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation of DNA-methyltransferase genes from strawberry (Fragaria × ananassa Duch.) and their expression in relation to micropropagation - Linlin Chang; Zhihong Zhang; Baiming Han; He Li; Hongyan Dai; Ping He; Hongzhe Tian (Plant Cell Reports, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

BREVIS RADIX is involved in cytokinin-mediated inhibition of lateral root initiation in Arabidopsis - Jing Li; Xiaorong Mo; Jirong Wang; Nannan Chen; Huan Fan; Chunyan Dai; Ping Wu (Planta, 2009)

Microcalorimetric Study on the Effect of Ce3+ on Halobacterium halobium R1 - Yi Liu; Jun Yin; Ran Li; Li Li; Jie Dai; Ye-Zhong Zhang; Ping Shen (Biological Trace Element Research, 2008)

A Novel Glycosylphosphatidylinositol-Anchored Alkaline Phosphatase Dwells in the Hepatic Duct of the Pearl Oyster, Pinctada fucata - Li-Ping Xie*; Yuan-Tai Wu*; Yi-Ping Dai; Qing Li; Rong-Qing Zhang (Marine Biotechnology, 2007)